Travel report for Dr Michael Baum visit to Syria 12-14 July 2022 - Baum, Michael (2023)
The Initiative lead Dr Michael Baum went to Syria to re-affirm support for the CGIAR-Syria relationship. Syria wishes to align with the F2R-CWANA Initiative, and there are two field stations that could be used as National Innovation Platforms to demonstrate and scale out new varieties and other innovations.